Multimode jetting unlocks a trade-off between nanostructure morphology and composition in focused electron beam induced deposition. (December 2019) - Kim, Songkil; Henry, Mathias; Moon, Young Hoon; Fedorov, Andrei G.
Graphical abstract: Abstract: An ability to accelerate the growth rate while simultaneously controlling shape and composition of deposits is fundamental to expanding the utility of electron beam assisted deposition for "direct write" nanostructure fabrication from gas phase precursors. We report on novel tunable mode of Focused Electron Beam Induced Deposition (FEBID) as enabled by the switchable use of reactive (O2 ) and inert (Ar) "assist" gases directed at high impingement energy and momentum to a deposition site concurrently with a supply of a precursor in a dual-nozzle FEBID arrangement. Organometallic molecules introduced into a deposition chamber in a free-molecular flow regime through a conventional gas injection nozzle, yielding a broad uniform substrate coverage by the precursor in a quasi-equilibrium adsorbed state. Simultaneously, a supersonic micro-jet from a micron-scale capillary placed in close proximity to a deposition site produces a low Knudsen number continuous flow impingement of energized "assist" gas, which perturbs the precursor state to facilitate different chemical reaction pathways. This process enables modulation of deposition outcomes, e.g., enhanced vertical growth rate (aspect ratio) of nanostructures when using argon micro-jet while locally removing parasitic carbonaceous by-products of organometallic precursor decomposition reaction by e-beam through interactions with oxygen micro-jet. Such in-situ/in operando (during growth and on-demand switchable) modulation of FEBID allows for rapid and precisely controllable deposition for a desired outcome, such as tuning metal-to-carbon composition and maintaining shape fidelity in fabricating high-aspect ratio composite nanostructures, which extends the capabilities of FEBID as a robust multi-dimensional, multi-purpose nanoscale 3D printing tool.